Pigment composition of the bright skin in the poison toad, Melanophryniscus rubriventris (Anura: Bufonidae) from Argentina - Bonansea, Maria Ines (2017)
The determination of the basis of skin colour is important to better understand the evolutionary and ecological relevance of colour variation in aposematic species. Significant variation in bright skin colouration can be found between and within populations of the poison toad, Melanophryniscus rubriventris. In this study, we identified the pigments present in the skin in seven populations of the species in Argentina to determine pigment composition of bright colouration. Our analysis showed that at least four different primary pigments consisting of a suite of orange-red carotenes and yellow xanthophylls contribute to the bright skin colour in different populations of the species. Four carotenoids, Astaxanthin, β-Carotene, Canthaxanthin, and Lycopene were detected by comparison with available standards in skin tissues on each population. Four carotenoids were also detected but not identified. We provide evidence that differences in colouration between individuals and populations in Melanophryniscus rubriventris cannot be merely ascribed to differences in their skin pigment profiles (i.e. pigment types). We discuss alternative explanations and stress the need of more studies on complex mechanisms and interactions affecting the expression of skin colouration in poison frogs and toads.